Old Testament law for Christians : original context and enduring application - Gane, Roy E., 1955-- (Grand Rapids, Michigan : Baker Academic, 2017)
"Christians have often neglected the wisdom of the Old Testament laws because they have been viewed as irrelevant, obscure, disturbing, or only useful as "moral laws". In Old Testament Law for Christians, Roy E. Gane, a leading evangelical expert in biblical law, helps readers understand the Old Testament law, how it functioned in the Old Testament, and how it is and is not instructive for contemporary Christians."
Conclusion: The value of obedience to God.
Includes bibliographical references and index.
Keywords: Law (Theology); Christianity and law